A doctrinal aspect of orientalism and its influences on Malay culture / Mohd Farhan Abd Rahman ... [et al.] - Abd Rahman, Mohd Farhan; Aziz, Nurul Hidayah; Che Ahmat, Amin; Yusof@Salleh, Muhammad Yusri; Abdul Rahim, Rahimin Affandi (2016)
History has stated on how British imperialized Malays by executing intervention policy in religion. The understandings of orientalist scholars are based on fundamental ideology of classical orientalist researches whom against Islam. This article focuses on analysis upon orientalists thought regarding Islamic influences unto Malay cultural life. The author explains approaches that have been applied by orientalists in evaluating Malays in Malaya, also secularism paradigm implementation on Malays’ thought as an explanation of how orientalist’s thought were designed. The author applies historical method, comparative and contents analysis to study those thoughts. The author also exercises natural approaches in order to create a research without any prejudices. The result of the study shows Islam is very influential in modeling Malays’ socio-cultural. Orientalist groups believe Malays has been influenced by cultural and living of Hinduism in every single lifestyle which includes local genius in building a civilization. This reason is the weakness of orientalist in understanding Malays due to conceptual background upon Euro-centrism. Thoughts were assumed upon European as a great and civilized nation compared to others and proudly present as an ambassador of civilization; who are the savior to the nation that supposed to be civilized.